Impact of Delaying the Addition of Anti-EGFR in First Line of RAS Wild-Type Metastatic Colorectal Cancer: A Propensity-Weighted Pooled Data Analysis - Palmieri, Lola-Jade; Buchler, Tomas; Meyer, Antoine; Veskrnova, Veronika; Fiala, Ondrej; Brabec, Petr; Baranova, Jana; Coriat, Romain (Cancers, 2022)
The first-line therapy of patients with RAS wild-type (WT) non-resectable metastatic colorectal cancer (mCRC) is usually 5-fluorouracil-based chemotherapy with either bevacizumab or an anti-epidermal growth factor receptor (EGFR). The addition of anti-EGFR antibodies is commonly delayed in clinical practice because of late RAS testing results. Our objective was to evaluate the impact on overall survival (OS) of a delayed anti-EGFR introduction strategy. This study pooled the data of two large retrospective studies. Patients with RAS WT non-resectable mCRC, treated in first line by a doublet chemotherapy with an anti-EGFR introduced with a delay of 2 to 4 cycles, were compared to an anti-EGFR and to an anti-VEGF that was introduced immediately. Patients numbering 305 in the delayed anti-EGFR group, 401 in the immediate anti-EGFR group, and 129 in the immediate anti-VEGF group were analyzed. After propensity scoring, there was no difference between the characteristics of the three groups. Median OS was 28.6 months (95% CI: 23.5-34.1) in the immediate anti-EGFR group, 35.1 (95% CI: 29.9-43.5) in the delayed anti-EGFR group, and 32.4 (95% CI: 25.4-44.8) in the immediate anti-VEGF group. There was no significant difference concerning median OS (p = 0.24) or progression-free survival (p = 0.56). This study suggests that delaying the introduction of an anti-EGFR has no deleterious impact on survival compared to the immediate introduction of an anti-VEGF or of an anti-EGFR.
Keywords: RAS status; anti-EGFR; bevacizumab; metastatic colorectal cancer